2020
DOI: 10.1021/acs.jpcc.0c02161
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Energy Control and Characterization of Nanoparticle Coatings

Abstract: Accurate and reproducible measurement of the structure and properties of high-value nanoparticles is extremely important for their commercialization. A significant proportion of engineered nanoparticle systems consist of some form of nominally core–shell structure, whether by design or unintentionally. Often, these do not form an ideal core–shell structure, with typical deviations including polydispersity of the core or shell, uneven or incomplete shells, noncentral cores, and others. Such systems may be creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 56 publications
(81 reference statements)
5
24
0
Order By: Relevance
“…This conclusion is in agreement with the complementary analysis in Müller et al, 8 which showed that all PTFE‐PS CSNP samples deviate from ideality as depicted in Figure 3B. The incomplete encapsulation of the core by the shell material in the case of the PTFE‐PS samples was also confirmed by Cant et al 15 In this work, the uncoated area fraction of the core for sample PTFE‐PS(3) was determined from SEM micrographs to be 12%. This is in excellent agreement with the value cov 1 of 15% calculated by the presented QUASES analysis.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This conclusion is in agreement with the complementary analysis in Müller et al, 8 which showed that all PTFE‐PS CSNP samples deviate from ideality as depicted in Figure 3B. The incomplete encapsulation of the core by the shell material in the case of the PTFE‐PS samples was also confirmed by Cant et al 15 In this work, the uncoated area fraction of the core for sample PTFE‐PS(3) was determined from SEM micrographs to be 12%. This is in excellent agreement with the value cov 1 of 15% calculated by the presented QUASES analysis.…”
Section: Resultssupporting
confidence: 91%
“…In Müller et al, 8 shell thicknesses were determined based on an analysis of XPS elastic peak intensities using the SESSA software, 2 and these values are similar to the thicknesses found here by the single island QUASES analysis. In a previous study, 15 Cant et al also determined a single PMMA overlayer thickness for the sample PTFE‐PMMA(1) by empirically fitting the XPS inelastic background and obtained d shell = 4.8 nm which is also close to the 5.5 nm found by the presented single‐island QUASES analysis.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…18 The importance of the method for this field is underlined by the number of articles and book chapters that have been published in recent years. [19][20][21][22][23][24][25][26][27][28] These publications not only report great advances but also point out the numerous challenges that must be considered in order to produce meaningful results with an XPS analysis of nanoparticles and nanoparticle coatings. SR-XPS has been successfully applied in the past to investigate the internal heterostructure of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%